Dark green religion : nature spirituality and the planetary future - Taylor, Bron Raymond (University of California Press, 2010)
"In this work, Bron Taylor examines the evolution of "green religions" in North America and beyond: spiritual practices that hold nature as sacred and have in many cases replaced traditional religions. Tracing a wide range of groups - radical environmental activists, lifestyle-focused bioregionalists, surfers, new-agers involved in "ecopsychology," and groups that hold scientific narratives as sacred - Taylor addresses a central theoretical question: How can environmentally oriented, spiritually motivated individuals and movements be understood as religious when many of them reject religious and supernatural worldviews?" "The "dark" of the title further expands this idea by emphasizing the depth of believers' passion and also suggesting a potential shadow side: besides uplifting and inspiring, such religion might mislead, deceive, or in some cases precipitate violence. This book provides a global tour of the green religious phenomenon, enabling readers to evaluate its worldwide emergence and to assess its role in a critically important religious revolution."--Jacket.